Factors That Influence The Relationship Between Nurses' Knowledge And The Implementation Of Basic Life Support In Hospital Emergency Installation - Nusdin, Nusdin; Riskawaty, Heni Marlina; Rispawati, Bq. Heni; Mesa, Nofita Dewi Kok; Andita, Rizki (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Basic Life Support (BHD) is skills crucial in save life patient stop heart or breath. Knowledge nurse about BHD plays a very important role in success implementation of BHD, especially in Installations Emergency Emergency (ER), where the condition critical often happen. Objective: To know factors that influence connection between level knowledge nurse with implementation of BHD in the emergency room sick. Research methods this use design descriptive analytic with cross-sectional approach. A sample of 60 nurses working in the ER was taken by purposive sampling. Data were collected through questionnaire that has been tested its validity and reliability, as well as sheet observation implementation of BHD. Data analysis was carried out using chi-square and regression tests logistics. Results: Research results show that there is connection significant between level knowledge nurse with implementation of BHD (p = 0.001). Other factors that influence connection the covering BHD training (p = 0.004), experience work (p = 0.018), and availability facilities (p = 0.030). Not found significant relationship​ between age (p = 0.451) and type gender (p = 0.672) with implementation of BHD. Conclusion: Knowledge nurse relate strong with implementation of BHD in the ER. Routine training, experience work, and adequate facilities​ support improvement quality implementation of BHD. It is recommended that the house Sick in a way periodic to organize BHD training and repair facility BHD supporters in the ER.